Pengujian Blackbox Testing Website Garuda Farm Menggunakan Teknik Equivalence Partitioning - Hardika, Bagus; Kurniawan, Mahesa Dzikri; Adzka, Muhammad; Prastowiyono, Daffarizqy; Banyubasa, Apik; Wicaksono, Aditya; Nasir, Muhammad (Jurnal Kridatama Sains dan Teknologi, 2024)
Software Testing is a critical aspect of ensuring the quality and performance of a system before its release. This study examines the Testing of the Garuda Farm website using the Black Box Testing method and the Equivalence Partitioning technique to detect errors within the system. The objective of this research is to identify errors in the blog menu system of the Garuda Farm website, ensuring that existing data is preserved before being utilized by the Admin. The Garuda Farm website is designed as a corporate profile, featuring functionalities such as login, registration, homepage, about page, product services, blog, and contact information. This study focuses on Testing the blog addition feature, which is frequently used to disseminate information through articles. The Equivalence Partitioning technique divides the input domain into data groups, encompassing both valid and invalid inputs, to ensure comprehensive Testing of each feature. The test results indicate that most features function according to specifications, with some exceptions related to input validation, such as blog creation dates and image uploads. Several errors were identified in handling invalid inputs, including the system’s inaccuracies in processing invalid dates and images. With a Testing validity rate of 56.25%, these findings provide recommendations for system improvements to enhance the quality and user experience of the Garuda Farm website. The implications of these findings suggest that improvements in input validation mechanisms, particularly for dates and images, can enhance system reliability and prevent the loss of critical data. Consequently, this would improve user experience and maintain the website’s credibility. Through the optimization of this Testing process, the Garuda Farm website is expected to enhance its credibility and competitive edge in the digital era